Sleep-disordered breathing in children with asthma: a systematic review on the impact of treatment - Sánchez T (Journal of Asthma and Allergy, 2016)
Trinidad Sánchez,1 José A Castro-Rodríguez,2 Pablo E Brockmann2,3 1Division of Pediatrics, School of Medicine, 2Department of Pediatric Cardiology and Pulmonology, Division of Pediatrics, School of Medicine, 3Sleep Medicine Center, Department of Neurology, School of Medicine, Pontificia Universidad Católica de Chile, Santiago, Chile Background: The objective was to perform a systematic review in order to describe the relationship between asthma and sleep-disordered breathing (SDB) in children, especially regarding the impact of treatment and management. Methods: We performed an electronic search in MEDLINE, EMBASE, and LILACS database. Study inclusion criteria were the following: 1) studies that examined the relationship between asthma/wheezing and SDB/obstructive sleep apnea (OSA); and 2) studies conducted in children <18 years of age. Primary outcomes were the prevalence of asthma and SDB, the tests used for diagnosis, and the influence of their treatment and management. Results: One thousand and twenty studies were identified, among which 32 were selected (n=143,343 children; 51% males; age [mean ± standard deviation] 8.4±2.5 years). Most studies (n=26) diagnosed SDB using questionnaires or clinical history. Nine studies performed a sleep study for diagnosing OSA. The diagnosis of asthma was based on clinical history (n=16), previous medical diagnosis (n=4), questionnaires (n=12), and spirometry (n=5). Children with asthma were more likely to develop habitual snoring and OSA, and children with SDB were more likely to develop asthma. Moreover, asthma was associated with more severe OSA, and the presence of SDB was associated with severe asthma. Treatment of SDB with adenotonsillectomy was associated with significant asthma improvement. Conclusion: The relationship between asthma and SDB appears to be bidirectional, and adenotonsillectomy appears to improve asthma control. Future trials on how asthma treatment could impact on SDB are needed. Keywords: obstructive sleep apnea, wheezing, children, Asthma, sleep-disordered breathing